СОВРЕМЕННЫЙ ВЗГЛЯД НА ПАТОГЕНЕЗ И ИНТЕНСИВНУЮ ТЕРАПИЮ ОСТРОЙ ЦЕРЕБРАЛЬНОЙ ИШЕМИИ - А. А. Фирсов; М. В. Смирнов; Т. А. Усанова; А. Ю. Кусакин; Н. А. Пятаев (Архивъ внутренней медицины)
Acute cerebral ischemia is an actual problem of modern angioneurology. As a result of pathogenetic mechanisms in acute cerebral ischemia occurs irreversible cell death, or an apoplectic depolarization of neurons. A promising direction in the treatment of ischemic stroke appears to search for effective combinations of drugs that affect different stages of the patobiochemical cascade in acute cerebral ischemia and stimulating regenerative processes in the nervous tissue.